Perancangan Jaringan Pada Client Server Menggunakan Aplikasi Cisco Packet Tracer - Susilawati Susilawati; Bayu Sasongkojati; Didik Aribowo (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2024)
Currently, the development of computer networks is progressing rapidly. Along with this, user demands for network quality are increasing, both LAN and WAN. Computer networking is the transmission of data (data communication) from the source computer (sender) to the destination computer (receiver) in the form of bits on the sending medium. The Cisco Packet Tracer application allows you to use simulated network data to provide information about the connectivity status of computers on your network when network connectivity problems occur. The method used is to look for references from various internet sources such as Google and YouTube. Simulate your network system using the Cisco Packet Tracer application. Cisco Packet Tracer is network simulator software introduced by Cisco Systems which functions as a learning, training and research medium for computer network simulations.